'A critical Analysis ' Grammarians' opinion on the use of "why ‘lama' for exception - Hussein, Ahmed bin Mohamed Abdel Fattah (Arab Journal for Sciences and Research Publishing, 2019)
This study intended to survey the grammarians' opinions toward sentenced used ‘lama’why' on the meaning of ‘ila’ " but " in signifying exception in favor of the opinions of grammarians and determining its significance. In addition, the study dealt with the different opinions of grammarians, and presented the evidences supported by El-Khalil and Sebaweh, which are adopted and approved by the majority of grammarians. The study introduced another opinion of grammarians which added another position where "‘lama’why " signifies exception supported by Quranic statements. The study showed the agreement and disagreement on those of second opinions. The study also presented other opinions regarding this issue. Some of these opinions agreed on the exception of "‘lama’why ", whereas other opinions neglected its significance.The study concluded that:1- " ‘lama’why " is an article of exception, even if this significance was only in two positions according to the majority of grammarians.2- The study showed that the appearance of "‘lama’why " meaning exception is not commonly used in Arabic speech.
Keywords: Exception tools; meanings